1998
DOI: 10.1007/s007010050147
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Velocity and Vasomotor Reactivity Before and after Shunting Surgery in Patients with Normal Pressure Hydrocephalus

Abstract: The purpose of this study was to evaluate pre- and post-shunting haemodynamic changes and their correlation with the clinical results in normal pressure hydrocephalus (NPH). Accordingly, eleven demented patients with clinical signs suggestive of NPH received examinations of cerebral blood flow velocity (BFV) and vasomotor reactivity (VMR) by transcranial Doppler sonography with carbogen testing before and after shunt treatment. Computerized tomography (CT), clinical assessment and neuropsychological grading we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…7,36 The increase of CBF after CSF diversion found in adult patients with idiopathic chronic hydrocephalus was ~ 50%, 39 whereas this increase was not significant in patients with NPH. 42,45 According to our study, progressive hydrocephalus in infants leads to greater reduction in CBF than it does in adults with idiopathic chronic hydrocephalus. This may be caused by the shorter existence of the hydrocephalus, the different consistency of the developing parenchyma in infants, and the higher vulnerability of the maturing periventricular white matter in infants.…”
Section: Discussionmentioning
confidence: 99%
“…7,36 The increase of CBF after CSF diversion found in adult patients with idiopathic chronic hydrocephalus was ~ 50%, 39 whereas this increase was not significant in patients with NPH. 42,45 According to our study, progressive hydrocephalus in infants leads to greater reduction in CBF than it does in adults with idiopathic chronic hydrocephalus. This may be caused by the shorter existence of the hydrocephalus, the different consistency of the developing parenchyma in infants, and the higher vulnerability of the maturing periventricular white matter in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a delayed diagnosis can result in irreversible degradation of the patient's cognitive potential. 34 For this reason, sensitive diagnostics ( Fig. 1) and prompt therapy (Fig.…”
Section: Outcomementioning
confidence: 99%
“…Others believe that a fall in cerebral blood flow is a secondary phenomenon resulting from a decrease in cerebral metabolism caused by a decrease in volume of brain tissue in normal pressure hydrocephalus (19–21). Some authors have found no alterations in cerebral hemodynamics after shunt therapy (6–8, 16), whereas others found significant improvement in cerebral blood flow (9–11) and cerebrovascular reactivity (7, 10–12), and a reduction in PI (13). A remarkable observation in our study was the decrease in blood flow velocities in patients with and without clinical improvement after shunt surgery, suggestive for a possible postoperative normalization in intraparenchymal pressure and concomitant relaxation of large arteries.…”
Section: Discussionmentioning
confidence: 98%
“…Whether changes in cerebral hemodynamics eventually lead to clinical improvement is unclear. The pathophysiologic mechanism underlying clinical improvement after shunt surgery in NPH is still unknown, and may include restoration of regional cerebral blood flow (7, 9–11, 16) and metabolic improvement (18). Higher preoperative cerebral blood flow, measured by means of single photon emission computed tomography, in patients with a favourable outcome has been observed (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation